Helium-implantation-induced lattice strains and defects in tungsten probed by X-ray micro-diffraction. (15th December 2018) - Das, S.; Liu, W.; Xu, R.; Hofmann, F.
Abstract: Tungsten is the main candidate material for plasma-facing armour components in future fusion reactors. Bombardment with energetic fusion neutrons causes collision cascade damage and defect formation. Interaction of defects with helium, produced by transmutation and injected from the plasma, modifies defect retention and behaviour. Here we investigate the residual lattice strains caused by different doses of helium-ion-implantation into tungsten and tungsten‑rhenium alloys. Energy and depth-resolved synchrotron X-ray micro-diffraction uniquely permits the measurement of lattice strain with sub-micron 3D spatial resolution and 10 −4 strain sensitivity. Increase of helium dose from 300 appm to 3000 appm increases volumetric strain by only 2.4 times, indicating that defect retention per injected helium is 3 times higher at low helium doses. This suggests defect retention is not a simple function of implanted helium dose, but strongly depends on material composition and presence of impurities. Conversely, analysis of W-1 wt% Re alloy samples and of different crystal orientations shows that both the presence of rhenium, and crystal orientation, have a comparatively small effect on defect retention. These insights are key for the design of armour components in future reactors where it will be essential to account for irradiation-induced dimensional change when predicting component lifetime and performance. Graphical abstract: Highlights: Helium-implantation causes large strains likely to reduce longevity of plasma-facing tungsten armour in fusion reactors. Non-linear defect retention (ten times dose increase only increases strain three times) suggests saturation regime onset. Little grain-orientation dependence means texture of tungsten armour can be optimised for other performance aspects. Not all transmutation elements strongly affect defect retention, e.g. 1% Re causes little increase in defect retention.